Optimization of Zinc(II) Adsorption Using Agricultural Waste - Ravindran, Gobinath; Radha Madhavi, M; Suleman Abusahmin, Bashir (International Journal of Engineering and Technology, 2018)
With industrial growth, presence of pollutants is growing enormously. Removal of pollutant from waste water and effluents can be accomplished by various techniques, out of which adsorption was found to be an efficient method. Applications of adsorption limits itself due to high cost of adsorbent. In this regard, a low cost adsorbent produced from palm oil shell based agricultural waste is examined for its efficiency to remove Zn (II) from waste water and aqueous solution. The influence of independent process variables like pH, residence time, initial solution concentration, activated carbon dosage and process temperature on the removal of Zn(II) by palm shell based activated carbon from batch adsorption process are studied systematically. The results reveal that palm shell based activated carbon can be an effective adsorbent for removal of Zinc (II) and is efficient compared to other types of adsorbent produced from agricultural waste.Â Â